Enhancement and analysis of TFRC performance for real-time data application: A survey - Mohamad Izril, Ishak; Mohd Alif Hasmani, Abd. Ghani; Ong, Bi Lynn (IEEE, 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/